ETHNOLINGUISTIC PECULIARITIES OF INVESTIGATING LANGUAGE UNITS: MEANS OF VERBALIZING THE CONCEPT OF “RATIONALISM” - Черська, Жанна; Гладкоскок, Леся (Видавничий дім «Гельветика», 2020)
This article examines the effectiveness of describing the concept of “rationalism” in journalistic texts. Modern journalism allows changes in the collective consciousness of its readership (and its surrounding society) as reflected in a text to be followed quickly, as well as the characteristics accompanying the formation of new trends in the development of concepts based on their means of verbalization to be identified. Despite attempts to distinguish ethnolinguistic methods for describing and analyzing material, ethnolinguistics primarily uses modern methods developed in other disciplines related to the study of semantic fields, frames, metaphors, and concepts. Accordingly, uncovering new approaches to the study of concepts from an ethnolinguistic perspective has evolved into a promising area of research at present, supplying both the purpose and objectives of this contribution. Taking into consideration the field approach to the study of the components of verbalization, according to which lexical units, which belong to different parts of speech are united by a common conceptual field, 12 means of verbalization relating to the concept of “rationalism” such as nouns, adjectives, and adverbs were selected from lexicographical sources: nouns – Rationalismus, Rationalist, Rationalistin, Vernunftmensch; adjectives – rational, rationalistisch, sinnvoll, vernünftig; adverbs – rational, rationalistisch, sinnvoll, vernünftig. Within the investigated sample all of the above-mentioned lexical units were recorded in combination with other components (568 examples) and the indicators of frequency of the means of verbalization were identified. The analysis of newspaper articles shows that the highest quantity of word uses was recorded for adjectives – 357 examples (62,8%), followed by adverbs – 136 lexical units (24%) and the lowest quantity of examples was found for nouns – 75 word uses (13,2%). As shown by quantitative indicators of “rationalism’s” verbalization as a concept, which to date, has not been sufficiently explored, modern journalism is dominated by adjectives, which carry a significative aspect of meaning, among which those most frequent encountered are the following combinations: rationales Verhalten, rationale Handeln, and rationale Entscheidungen.
Лінгвокультурологічні особливості дослідження мовних одиниць: засоби вербалізації концепту «Раціоналізм»
Keywords: linguistic world image; concept,; component of verbalization,; ethnolinguistic analysis